Cyclin dependent kinase 4 and 6 inhibitors as novel therapeutic agents for targeted treatment of malignant mesothelioma - Sobhani, Navid (Genes Cancer, 2017)
Malignant Mesothelioma (MM) is a rare and aggressive form of tumour that affects the lining of the internal organs for which current treatments have not been proven to be very effective. P16(INK4A) tumour suppressor encoding CDKN2A gene is often downregulated in MM. This protein is a cyclin dependent kinase 4 and 6 inhibitor, that normally phosphorylates RB1, which has to be un-phosphorylated in order to block cell-cycle at G1 in normal cells. Adding CDK inhibitor molecules to MM in pre-clinical studies has been proven to restore the normal function of p16(INK4A), blocking thereby MM cell cycle at G1. Future randomised phase III studies with CDK4/6 inhibitors in MM carrying relevant CDK4/6, cyclin D1/3 or p16 aberrations will be warranted.